Prioritization of e-Government strategies using a SWOT-AHP analysis:: the case of Turkey - Kahraman, Cengiz; Demirel, Nihan Cetin; Demirel, Tufan (TAYLOR & FRANCIS LTD, 2007)
The e-Government agenda is being pursued throughout the world to one degree or another, but it has added significance in Central Europe. The region is just beginning to emerge from a period of far-reaching political and economic transformation following the collapse of repressive communist systems. For these countries, e-Government is more than simply a new channel of delivering services; it offers an opportunity to achieve a quantum leap in transparency and efficiency of administration, which the region's leaders have promised their citizens since the early 1990s. Turkey is currently working hard to catch this opportunity. Turkish Government has initiated the Urgent Action Plan in December 2002 to remedy long-lasting economic problems and to improve social and well-being of the country. One of the basic components of this plan is 'e-Transformation Turkey Project' which aims to carry Turkey into Information society. One of the two purposes of this study is to define and to prioritize the strengths, weaknesses, opportunities, and threats ( SWOT) groups and their subfactors for e-Government in Turkey. The other purpose is to determine and to evaluate the alternative strategies for e-Government applications at the national level in Turkey. We use the SWOT approach in combination with analytic hierarchy process (AHP) to achieve this task. The strategies have been prioritized and sensitivity analyses of the obtained results have been made using a software.
Keywords: e-Government; SWOT; analytic hierarchy process; strategic planning; sensitivity analysis; SERVICES; INNOVATION; FRAMEWORK; TOOLS; Computer Science; Information Science & Library Science; Business & Economics